Boys at Play: Football in Elementary Schools - Colm Kerrigan (Educate~, 2006)
This article focuses on the contribution of schoolboy football to three aspects of elementary education in late nineteenth and early twentieth century London schools. These are its benefits individually and collectively to scholars who played it, its role in promoting improved relationships between scholars and teachers in elementary schools and the role of football in identifying these schools as educational institutions that were to become focal points of local communities. Sources investigated include the records of schoolboy football associations, school log books, newspaper reports, published autobiographies of players and a ‘Special Report’ by the Education Department on the voluntary work of teachers in promoting games as extra-curricular activities in elementary schools. While the benefits to health, character training and social development of the boys who played football at their elementary schools are difficult to assess a century later, it is concluded that the value of learning football skills at an early age was important for their proficiency at the game. The extent of the improved relationships between teacher and taught that followed the introduction of football, although exaggerated by some games advocates, was nevertheless likely to have been significant. Finally, by the time of World War One, elementary-school football had helped identify the elementary school as an established and recognised part of the local community.